The value of disclosing IPR to open standard setting organizations - Katrin Hussinger; Franz Schwiebacher (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Open standard-setting organizations (SSOs) have emerged as important coordination and diffusion mechanism for information and communication technologies. Open standards are developed non-discriminatorily and licensed to anybody at reasonable and non-discriminatory terms. Little is known about the value of IP contributions to open standards for technology providers. This paper provides a large-scale empirical assessment thereof. Our findings show that disclosure of standard-relevant IP ownership is valued positively by financial markets only if the disclosure refers explicitly to associated patents. The loss of exclusivity to IPR appears to be outweighed by the expected benefits from open standards. Patents appear to signal the technological quality of IP contributions from firms with low R&D intensities.
urn:nbn:de:bsz:180-madoc-346220
Keywords: O32; O34; L15; 330; Open standards; IP disclosures; market value